PENGGUNAAN TINDAK TUTUR ASERTIF DALAM PEMBELAJARAN TEKS EKSPOSISI DI MTS MA’ARIF NU 01 GANDRUNGMANGU - Icha Fina Fanesha; Gigit Mujianto (Universitas Muhammadiyah Surabaya, 2024)
Acts of assertive speech have the main purpose of making it easier to inform things. The purpose of this study is to describe 1) the forms of assertive speech at Mts Ma 'arif nu 01 gandrungmangu, 2) the assure-language delivery strategy at Mts Ma 'arif nu 01Gandrungmangu, and 3) steps for learning exposition text at Mts Ma'arif Nu 01 Gandrungmangu. The method used in this research is the descriptive qualitative method. The data used in the study is to analyze speech that contains both assertive speech and expounding text study steps. Data collection techniques are in the form of literature study techniques and note-taking techniques. Data analysis techniques are applied to determine data, classify data, describe data, and draw conclusions from research results. Research indicates that there are six forms of assertive speech found in the video study of the expounding text expressing, telling, suggesting, pride, complaining, and demanding. There are four strategies for expressing literal speech, that is, direct speech, indirect speech, literal speech, and unliteral speech. Forms and strategies for the articulation of action are found in the learning process based on the meaning of speech, and the context contained in the teacher's speech. In every form and strategy, original-language delivery has a different purpose and purpose. Then there are four assertive speech strategies, and there are four exposition text learning steps.